Survey: Models and Prototypes of Schema Matching - Edhy Sutanta; Retantyo Wardoyo; Khabib Mustofa; Edi Winarko (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Schema matching is critical problem within many applications to integration of data/information, to achieve interoperability, and other cases caused by schematic heterogeneity. Schema matching evolved from manual way on a specific domain, leading to a new models and methods that are semi-automatic and more general, so it is able to effectively direct the user within generate a mapping among elements of two the schema or ontologies better. This paper is a summary of literature review on models and prototypes on schema matching within the last 25 years to describe the progress of and research chalenge and opportunities on a new models, methods, and/or prototypes.